The role of physiotherapy in fibromyalgia: Current and future perspectives - Antunes, Mateus Dias; Marques, Amélia Pasqual (Frontiers in Physiology, 2022)
Fibromyalgia is a chronic pain condition characterized by generalized musculoskeletal pain, hyperalgesia and allodynia, commonly associated with other symptoms such as fatigue, poor sleep quality, anxiety and depression. The clinical manifestations of this rheumatic disease have significant psychosocial and economic repercussions, with a substantial impact on health status, quality of life and social activities. Currently, recommendations for the management of fibromyalgia include patient education and non-pharmacological interventions, and among the indicated treatments, clinical guidelines include several physiotherapeutic resources, essential for individuals affected by this syndrome. Research in the physiotherapy field has demonstrated its effectiveness, but there is a need to update the literature. This study aims to identify the effectiveness of physiotherapy in the treatment of individuals with fibromyalgia. We performed a literature review looking for articles dated from March 2012 to March 2022 using the terms “fibromyalgia”, “physiotherapy”, “physical therapy”, “rehabilitation” in different languages in various databases and their main information was read and collected and presented in a descriptive way. The effects of physiotherapy interventions are summarized in order to provide a reference for future research and clinical application. Research on non-pharmacological physiotherapy-oriented treatments has grown in recent years as an alternative for fibromyalgia treatment. This review allows fibromyalgia patients to receive appropriate physical therapy interventions to promote their health.